Information in Social Media as Source of News based on Age and Educational Background - Azfa Roslan; Nafis Taupek (Human Sustainability Procedia, 2022)
This research is done to study the relationship of variables. This research focuses on proving the relationship between information in social media and sources of news. This research also uses age and level of education on finding out if the information searched online is different. This research uses Agenda Setting Theory. In the process of completion of this research, a set of questionnaires was used and distributed to 140 respondents which are amongst social media users. This study approves the relationship between information in social media and sources of news. However, the result also showed that there is no difference in terms of search information between age and level of education.